Macromol. Mater. Eng. 7/2016. Issue 7 (July 2016) - Isık, Tuğba; Horzum, Nesrin; Yıldız, Ü. Hakan; Liedberg, Bo; Demir, Mustafa M.
Abstract : Back Cover: An easy‐to‐use test platform toward the rapid diagnosis of many life‐threating diseases was developed. DNA was isolated from the mixture of BSA+DNA using fibrous commodity polystyrene, which was extremely cheap and can be readily electrospun under ambient conditions. Surface modification with Au nanoparticles improved the performance of the fibrous membrane. Further details can be found in the article by Tuğba Isık, Nesrin Horzum, * Ü. Hakan Yıldız, Bo Liedberg, and Mustafa M. Demir* on page 827.